The design of the visual communication mediums, movie posters: semiotic analyses of the posters of the movie “Recep Ivedik 4” - Kavuran, Tamer; Çetinkaya, Ali (My University, 2015)
Human beings have developed many methods and techniques to solve the communication problem that is one of the most important needs. One of these means is the ‘posters’. Posters are important means of communication and are products of graphic design. This requires that a poster must be esthetical as well as functional. Posters are at the same time products of visual communication with artistic value. The design of them is important like it is the case in many other products, because posters reach massive people with their artistic values and beauty of their presentations and their being functional, and contribute greatly to the interaction among people and to the development of visual communication. Posters carry these characteristics and are divided into various types among them. One of these types is the cultural and artistic posters. Film posters are considered in this type. One of the characteristics that make movie posters interesting and special as a means of communication is that they are traveling from city to city, from one country to another country while they are playing their part as a means of communication, and more important than this, their being universal.
Kitap - Kitap İçinde Yayın (Bölüm ya da Makale)
Baltic Institute of Humanities
Keywords: Poster; Semiotics; Film